91-(6x+15)=6(x+4)+x

Simple and best practice solution for 91-(6x+15)=6(x+4)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 91-(6x+15)=6(x+4)+x equation:


Simplifying
91 + -1(6x + 15) = 6(x + 4) + x

Reorder the terms:
91 + -1(15 + 6x) = 6(x + 4) + x
91 + (15 * -1 + 6x * -1) = 6(x + 4) + x
91 + (-15 + -6x) = 6(x + 4) + x

Combine like terms: 91 + -15 = 76
76 + -6x = 6(x + 4) + x

Reorder the terms:
76 + -6x = 6(4 + x) + x
76 + -6x = (4 * 6 + x * 6) + x
76 + -6x = (24 + 6x) + x

Combine like terms: 6x + x = 7x
76 + -6x = 24 + 7x

Solving
76 + -6x = 24 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
76 + -6x + -7x = 24 + 7x + -7x

Combine like terms: -6x + -7x = -13x
76 + -13x = 24 + 7x + -7x

Combine like terms: 7x + -7x = 0
76 + -13x = 24 + 0
76 + -13x = 24

Add '-76' to each side of the equation.
76 + -76 + -13x = 24 + -76

Combine like terms: 76 + -76 = 0
0 + -13x = 24 + -76
-13x = 24 + -76

Combine like terms: 24 + -76 = -52
-13x = -52

Divide each side by '-13'.
x = 4

Simplifying
x = 4

See similar equations:

| 7x+17-5x+17=6 | | 21-8=x | | 5x-30=5x+30 | | 2m-m=13+16 | | 0.3(-0.9+8x)=3.2x | | 0.15-0.03(x+2)=-0.01(3-x) | | 1.33n+2n=-6.33+1.75n | | 8x+4x+7y=180 | | 2.4=14.4 | | 12x+(4x-1)=36 | | 1x+8=3 | | 7+9y=19-3y | | 12x-6x+204=12x+120 | | 2(d+7)= | | 6-2x(x+6)=3x+4 | | 6(2+5x)=12 | | 2a=a+11 | | -2-4x+8=-3(2-x)+4(8x+3) | | 8=8X+16+8X | | (x^4)+(x^2)-42=0 | | -91=9+8 | | 2y-4=2y-3 | | 52+180w=2(26+90w) | | 6x-5=1x+5 | | 2(8x+2)=3(2x-7)-5 | | 2(2-y)/5=-y | | 9v-4v=20 | | 3y-10=-2(6-y) | | 6(x+4)+3x-2=54 | | 2y-4=71-105y | | -208+11x=-5x+128 | | 2m+s=465 |

Equations solver categories